Multimodal magnetic resonance imaging on brain structure and function changes in subjective cognitive decline: a mini-review - Yue, Jinhuan; Han, Shengwang; Li, Ang; Wei, Zeyi; Cao, Danna; Gao, Shenglan; Li, Xiaoling; Yang, Guanhu; Zhang, Qinhong (Frontiers in Aging Neuroscience, 2023)
Subjective cognitive decline (SCD) is the initial stage of Alzheimer's disease (AD).Early identification of SCD and its risk factors is of great importance for targeted interventions and for delaying the onset of AD. We reviewed the relevant literature on structural magnetic resonance imaging (sMRI), diffusion tensor imaging (DTI), functional magnetic resonance imaging (fMRI), and other techniques regarding SCD research in recent years. This study applied sMRI and fMRI techniques to explore abnormal brain structures and functions, which may help provide a basis for SCD diagnosis.